Generation of a new human induced pluripotent stem cell (hiPSC) line from a South Asian Indian with a MYBPC3Δ25bp variant - Prasanth Chimata; Deepak K Kashyap; Thiagarajan Sairam; Akshayaa Ganesh; Kumarasamy Thangaraj; Meera Purushottam; Biju Viswanath; Sanjeev Jain; Perundurai S Dhandapany (Stem Cell Research, 2022)
Myosin binding protein C3 (MYBPC3) is a thick filament contractile protein that interacts with myosin, titin and actin and regulates cardiac muscle contraction. Genetic variations in the MYBPC3 gene are known causal factors for cardiomyopathy and heart failure. Previously, we identified a recurrent MYBPC3 deletion (25 base pairs) among South Asians associated with cardiomyopathy and heart failure. Here, we generated an induced pluripotent stem cell (iPSC) line using peripheral blood mononuclear cells (PBMC) from an Indian harboring MYBPC3 deletion. This iPSC line displayed embryonic stem cell morphology, expressed pluripotency markers, differentiated into three germ layers and exhibited normal karyotype.